2008
DOI: 10.4315/0362-028x-71.1.200
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities Associated with Retail Alfalfa Sprouts

Abstract: Fresh produce, including salad, is increasingly implicated in foodborne outbreaks. Although studies have been carried out to detect specific human pathogens from fresh produce, the total bacterial community associated with fresh produce is poorly understood. In this study, we characterized the bacterial community associated with alfalfa sprouts, using a culture-independent method. Four retail-purchased alfalfa sprout samples were obtained from different producers, and the bacterial community associated with ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
4
10
0
Order By: Relevance
“…This suggests sufficient sampling with total microbial flora being represented by identified phyla and genera. Similar curves have been reported earlier for alfalfa sprout and chicken caeca microflora 30,31 . Chicken had higher bacterial diversity and species richness than mung sprout.…”
Section: Metagenomic Analysis Of Microbial Diversitysupporting
confidence: 89%
See 3 more Smart Citations
“…This suggests sufficient sampling with total microbial flora being represented by identified phyla and genera. Similar curves have been reported earlier for alfalfa sprout and chicken caeca microflora 30,31 . Chicken had higher bacterial diversity and species richness than mung sprout.…”
Section: Metagenomic Analysis Of Microbial Diversitysupporting
confidence: 89%
“…There are very few reports on microbiological diversity of different food samples studied by HT-NGS. Moreover, the available reports on metagenomics have identified limited microbial diversity in alfalfa sprouts, chicken caeca, gut 30,43,44 without much emphasis on pathogenic nature. V3 region was targeted and the total microbial diversity characterized up to species level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plating experiments indicated that the microbiological quality and character of the sprout samples we used in this work were typical of this food, as reported previously [3,32,33,34,35]. Specifically, mesophilic plate counts for three separate packages of retail alfalfa sprouts sampled over a period of 4 months ranged from 3. .…”
Section: Cultural and Molecular Characterization Of Endogenous Sproutsupporting
confidence: 73%